Quality assessment of histopathological stainings on prolonged formalin fixed thrombus tissues retrieved by mechanical thrombectomy - Bilgin, Cem; Dai, Daying; Johnson, Collin; Mereuta, Oana M.; Kallmes, David F.; Brinjikji, Waleed; Kadirvel, Ramanathan (Frontiers in Neurology, 2023)
Background Formalin-fixed retrieved clots from mechanical thrombectomy (MT) are now routinely studied using both conventional histopathologic techniques and immunohistochemistry (IHC). However, the effects of prolonged formalin fixation on the histological results of clot analysis remain unknown. The objective of this study was to investigate the effects of prolonged formalin fixation on quality of histopathologic stainings of thrombus tissues retrieved by MT. Methods As part of the multicenter EXCELLENT registry, a total of 80 clots extracted by MT from acute ischemic stroke patients were randomly selected from the tissue database and assigned into four groups according to 10% neutral buffered formalin (NBF) fixation duration (1–30, 30–60, 60–90, and 90+ days, up to 2 years). Samples underwent processing and sectioning. Two serial sections for each case were stained with hematoxylin and eosin (H&E), Martius Scarlet Blue (MSB), and IHC for CD42b (platelet marker). An expert pathologist, who was blinded to tissue fixation duration and patient clinical data, assessed the quality of each stain including stainability, sensitivity, specificity, and consistency of stainings. Results No significant issues were encountered during tissue processing and sectioning. On H&E stain, 97.5% (78/80) of slides showed good-quality staining, demonstrating clear histological properties of the thrombus tissue as red blood cells (RBC) stained in red, fibrin/platelet stained in pink, and nuclei stained in blue with intranuclear detail. The same histological features were also successfully demonstrated on MSB for all 80 samples. One of the 80 samples (1.2%) showed that RBC lost stainability on H&E due to tissue autolysis. Clear positive signal of platelet staining was expressed in 98.8% of the samples (79/80) with minimal background staining on IHC. There was no significant difference in staining quality across different formalin fixation groups. Conclusion A good quality of histopathological staining is achievable for the thrombus tissue fixed in 10% neutral buffered formalin for up to 2 years. The findings are limited to the thrombus tissue retrieved by MT and specific fixation and staining protocols used in the study. To apply these results to other tissue or experimental setups, further studies and validations would be necessary. Clinical trial registration This study was conducted as part of the EXCELLENT study: www.clinicaltrials.gov, unique identifier: NCT03685578.